Fundamental Beliefs, Origin Explanations and Perceived Effectiveness of Protection Measures: Exploring Laypersons' Chains of Reasoning About Influenza - Véronique Eicher; Alain Clémence; Bangerter, Adrian; Audrey Mouton; Eva G. T. Green; Ingrid Gilles (My University, 2013)
ABSTRACTLaypersons' chains of reasoning in explaining recent influenza outbreaks are investigated. Drawing on social representations theory, fundamental worldviews, that is, the belief in a dangerous world (BDW), are postulated to anchor explanations of disease origins, which in turn affect perceived effectiveness of protection measures. Our study, based on a longitudinal survey among the general public in Switzerland, showed that the lower people's BDW scores, the more they appeal to natural origins to explain outbreaks and the more they perceive official protection measures as effective. The higher people's BDW scores, the more they explain outbreaks via hygienic origins, which are linked with out‐group discrimination measures, and conspiracy origins, which are linked with lower perceived effectiveness of aid intervention measures. Copyright © 2013 John Wiley & Sons, Ltd.